The Compilation of Electronic Dictionaries for the African Languages - Smit, Maria (Lexikos, 2000)
Abstract: The distinction between encyclopedic and semantic knowledge is well-known. The influential Gennan meta lexicographer, Wiegand, also identifies a third kind of knowledge, which he calls special-field object-constituting knowledge. It is precisely this kind of knowledge users need in order to know to which object a particular lexical item refers, otherwise they cannot use that lexical item referentially in communication. This article focuses on Konerding and Wiegand’s (1994) discussion of frames and on their suggestions with regard to frame-based dictionary articles. Certain types of information are of great importance if the object-constituting knowledge is to be conveyed in dictionary articles. The article also investigates the possibilities of using frames in special-field lexicography. A sample article from an ethnomusicological database is presented in which the frame for artefacts, as worked out by Konerding, is applied and discussed. By means of frames, lexicographers can systematically ensure that the special-field object-constituting knowledge is indeed present in the articles they write. Keywords: SPECIAL-FIELD LEXICOGRAPHY, FRAME THEORY, FRAMES, LEARNER’S DICTIONARlES, SPECIAL-FIELD ENCYCLOPEDIC DICTIONARlES, SPECIAL-FIELD OBJECTCONSTITUTING MEANING KNOWLEDGE, MATRIX FRAMES, MINIMAL FRAMES, ITEM CLASSES, PREDICATE CLASSES Opsomming: Die gebruik van rame in vakensiklopediese leksikografie: ’nEtnomusikologiese gevallestudie. Die onderskeid tussen ensiklopediese en semantiesekennis is welbekend. Die invloedryke Duitse metaleksikograaf, Wiegand, identifiseer ook ’n derdetipe kennis, wat hy vakensiklopediese objek-konstitutiewe kennis noem. Di.t is juis hierdie 500rtkennis wat gebruikers nodig het om te weet na watter objek ’n bepaalde leksikale item verwys,anders kan hulle nie die leksikale item in ’n verwysende funksie in kommunikasie gebruik nie.Hierdie artikel fokus op Konerding en Wiegand (1994) se bespreking van rame en hulle voorstellein verband met raam-gebaseerde woordeboekartikels. Sekere tipes inligting is van uiterstebe lang om objek-konstitutiewe kennis in woordeboekartikels weer te gee. Die artikel ondersoekook die moontlikhede om rame in vakleksikografie te gebruik. ’n Voorbeeldartikel uit ’n etnomusikologiesedatabasis word aangebied, waarin die- raam vir artefakte, soos uitgewerk deur Konerding; toegepas en bespreek word. Oeur middel van rame kan leksikograwe op ’n sistematiese wyseseker maak dat die objek-konstitutiewe kennis inderdaad in die artikels wat hulle skryf, aanwesigis. Sleutelwoorde: VAKLEKSIKOGRAFIE, RAAMTEORIE, RAME, AANLEERDERWOORDE_BOEKE, VAKENSIKLOPEDIESE WOORDEBOEKE, VAKENSIKLOPEDIESE OBJEK-KONSTITtITIEWEBETEKENISKENNIS, MATRIKSRAME, MINIMALE RAME, ITEMKLASSE, PREDIKAATKLASSE